The Standardization Process as a Chance for Conceptual Refinement of a Disaster Risk Management Framework: The ARCH Project - René Lindner (MDPI AG, 2021)
Risks related to climate change and natural hazards increasingly affect urban areas such as historic towns, old urban quarters, villages, and hamlets. These, as well as historic landscapes, make up a significant part of an urban area’s identity and cannot just be rebuilt or significantly changed without taking into account the historic value, cultural background, and prescribed regulations. Systematic resilience building for historic areas is becoming essential, and research supporting it will be in the spotlight. However, questions still exist concerning how to best transfer research results into practice at the community level. Standardization of resilience-enhancing methods and tools deriving from research projects is one option, chosen, e.g., for the EU-Horizon 2020 project ARCH. Within the project, a disaster risk management (DRM) framework has been composed and then transferred into a standard, supported by a co-creation approach involving relevant stakeholders. This article outlines the project’s different standardization steps and its impact on the development of the ARCH DRM Framework. It highlights the systematic inclusion of project-external stakeholders who actively contribute to the validation and enhancement of the ARCH DRM framework to guarantee maximum applicability in historic areas, supporting them in their fight against the impacts of climate change and natural hazards.